Anthropometric Comparison of Cephalic Indices between the Jhar and Sayawa Ethnic Groups in Tafawa-Balewa Local Government Area, Bauchi State, Nigeria - Salman J. I; Muhammad M; Musa B; Kumurya H.S; Madugu U.M; Caleb A.D; Auwal H; Alfred A.W; Tongle N.J; Mosugu O.O; Dauda I.M; Shuaibu S (Darul Yasin Al Sys, 2026)
Cranial morphology assessed through anthropometric indices is fundamental for understanding population diversity, forensic identification, and clinical assessment, particularly within Nigeria’s multi-ethnic context. This cross-sectional study aimed to compare cephalic indices—defined as the ratio of maximum head breadth to maximum head length—between the Jhar and Sayawa ethnic groups in Tafawa-Balewa Local Government Area, Bauchi State, Nigeria, and to generate baseline reference data for these populations. A total of 410 participants (103 Jhar and 307 Sayawa), aged 5–66 years (mean = 24.0 ± 11.2; 291 males and 119 females), were recruited, and socio-demographic information was obtained using a structured pro forma. Head length and breadth were measured following standardized anthropometric techniques, and cephalic indices were calculated accordingly. Data were analyzed using Microsoft Excel and SPSS (Version 27), with descriptive statistics, charts, and tables for presentation, and categorical associations evaluated using Chi-square tests (p < 0.05). The mean cephalic index was 79.33 ± 4.85 for Jhar and 78.32 ± 5.19 for Sayawa, values that fall within the mesocephalic range indicative of intermediate head shapes typical of populations in the region. No statistically significant differences were observed between the two ethnic groups (p > 0.05), suggesting a broadly shared cranial profile. These findings enrich the anthropometric database for Nigerian ethnic groups and have practical implications for forensic anthropology, clinical assessment, and future research on craniofacial variation in multi-ethnic populations.